A systematic review exploring the evidence reported to underpin exercise dose in clinical trials of rheumatoid arthritis. (11th August 2020) - Boniface, Graham; Gandhi, Varsha; Norris, Meriel; Williamson, Esther; Kirtley, Shona; O'Connell, Neil E
Abstract: We aimed to evaluate the evidence reported to underpin exercise dose in randomised controlled trials (RCTs) using strengthening exercise in RA. We searched six different databases between 1 January 2000 and 3 April 2019. We included RCTs, where a main component of the intervention and/or control used strengthening exercise. Evidence sources cited to underpin dose were judged for their quality, consistency and applicability. Thirty-two RCTs were reviewed. Four (12.5%) piloted the intervention without using dose-escalation designs to determine optimal dose-response. Twenty (62.5%) reported no evidence underpinning dose. Where reported, quality, consistency and applicability of the underpinning evidence was a cause for methodological concern. The majority of RCTs did not report the evidence underpinning dose. When reported, the evidence was often not applicable to the clinical population. Frequently, the dose used differed to the dose reported/recommended by the underpinning evidence. Our findings illustrate exercise dose may not be optimised for use with clinical populations prior to evaluation by RCT.